Phase coherent states for enhancing the performance of continuous variable quantum key distribution - Becir, A; Wahiddin, Mohamed Ridza (The Physical Society of Japan, 2012)
In this paper, we present three continuous variable quantum key distribution protocols (named two-, four-, and eightstate protocols) based on the discrete modulation of phase coherent states. We investigate the security of these protocols against the collective eavesdropping attacks and show their performance in a realistic setup by taking into consideration the realistic lossy noisy quantum channels, and the imperfection of detection. We show that the use of phase coherent states gives better performance in terms of noise tolerance, key rate, and achievable distance than that of common linear coherent states.